Public Private Partnerships on Public Financial Management Reforms in Asia : Opportunities and Lessons - World Bank Group (World Bank, Washington, DC, 2017)
The growing investment needs in the South Asia Region (SAR) and East Asia and Pacific Region(EAP) necessitate high quality public financial management in order to sustain the growth momentumand achieve the desired development objectives. As these regions operate within limited fiscalspace for development, efficient public financial management is essential to achieve the best results for every dollar spent. However, challenges persist in implementing timely reforms in Public Financial Management (PFM), building ownership to drive reforms and strengthening capacity to implement, embed and sustain such reforms.This PFM retrospective study uses a two-pronged approach. It illustrates examples of good practices of partnerships in financial management reforms between the public and the private sector and draws lessons learned from effective financial management reforms in the private sector in SAR and EAP. The study cites country specific examples through case studies from the following countries (listed in alphabeticalorder) India, Indonesia, Malaysia, Pakistan and Sri Lanka, where collaboration between the public sector and private sector have contributed to successful public financial management reforms. While exploring these various forms of public-private collaboration, it also looks at additional types of partnerships such as with peer institutions in other countries, development partners and regional groups. The study identifies the enabling environment conducive to collaboration. Three significant factors pertinent to the cases are covered in detail, namely: (1) windows of opportunity; (2) leadership and change agents; and (3) the institutional environment. The development strategies of the governments covered in the cases, such as the New Economic Model of Malaysia, are considered as windows of opportunity for private sector involvement as they led to scaling up of PFM reforms and created the need to collaborate with the private sector to implement reforms. In particular, the following organizations and individuals stand out in the case studies as leaders and change agents that connect the public and private sectors to move the PFM reform agenda forward: Director, Department of Municipal Administration—state of Karnataka; a combination of high and working level champions of reforms from the Indonesian Ministry of Finance (MoF);the Institute of Chartered Accountants of Sri Lanka (CA Sri Lanka) and its public sector wing staff and council members; the Secretary General of the Treasury and the Accountant General in Malaysia; and the past and current Auditors General in Pakistan and Sri Lanka.